Depression and Anxiety among COVID-19 Patients in Jordan: A Cross-sectional Comparison between Inpatients and Outpatients - Mahmoud Bashtawi; Rawan Masri; Mohammad Nusair; Raed Ibdah; Mohammad Diabat; Tareq Al-zoubi (Jordan University of Science and Technology, 2024)
Background: Many studies have shown increased levels of anxiety and depression during the COVID-19 pandemic. Objectives: This study assesses anxiety and depression among COVID-19 patients who received treatment in outpatient and inpatient settings in Jordan. Methods: This cross-sectional study involved 236 individuals who tested positive for COVID-19 and received care at the hospital either as inpatients or outpatients at King Abdullah University Hospital (KAUH) in Jordan from April 9th to September 21st of 2021. The Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) were used as standardized assessments to evaluate these symptoms. Results: Our results indicated minimal anxiety and mild depression overall, with outpatients scoring significantly higher on both scales than inpatients (p-value= 0.011). Factors leading to higher depression and anxiety scores included chronic diseases, a family history of mental health issues, COVID-19 related worries, experiences of social ostracism or bullying, inadequate government support, unemployment, daily following of COVID-19 news, and being female. Participants aged 29-44 and those who previously consulted a psychiatrist also had higher anxiety scores. Conclusions: The findings suggest greater anxiety and depression among outpatients, linking these conditions to sociodemographic factors and COVID-19 experiences. The study underscores the need for healthcare systems to address the mental health of COVID-19 patients and combat misinformation's impact on emotional well-being. Implications for Nursing: Nurses play a pivotal role by integrating routine mental health assessments, particularly for those with identified risk factors, and addressing both physical and mental health needs, emphasizing the necessity of a holistic approach to patient care.